The investigation of microbial-intestinal epithelial cell interactions in the gut and their effects on inhibitor of apoptotic proteins (IAPs) - Dykstra, Natalie (University of Ottawa (Canada), 2008)
Probiotic bacteria such as Lactobacillus plantarum strain 299v (Lp299v) have been shown to upregulate facets of innate immunity. This study assessed whether Lp299v prevents apoptosis in intestinal epithelial cells (IECs) when faced with cytokine challenge. Both in vitro and in vivo systems were exposed for a pre-determined time to Lp299v or strain Lpadh---a non-adherent derivative of Lp299v. HT-29 cells were then challenged with cytokine mixture (TNF-alpha, IFN-gamma, and IL-1a) to imitate conditions of inflammation. To assess for apoptosis, we evaluated both TUNEL analysis and caspase activity assays. Results of the assays indicate a marked decrease in apoptosis in samples treated with Lp299v. The adherent negative Lpadh-strain showed similar but less pronounced prevention of cytokine-induced apoptosis. IAPs were assessed both in vitro and in vivo and HIAP1 and HIAP2 were determined to be involved in this process. This is consistent with NF-kB activation by Lp299v. Probiotics may confer exogenous effects on IECs to elaborate protective mechanisms and alter cell homeostasis through alteration of caspase-dependent apoptosis.
Keywords: Biology, Cell.; Chemistry, Biochemistry.